Ultraviolet-absorbing polyester film, polarizing plate
By combining a cyclic imide ester-based ultraviolet absorber with a PET resin derived from biomass resources, the problem of excessive foreign matter and resin deterioration in the production of polarizing plate protective films using biomass PET resin has been solved, achieving high transparency and Low foreign matter polyester film suitable for polarizing plates and image display devices, promoting sustainable development.
Patent Information
- Application Number
- CN202380046506.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-14
- Filing Date
- 2023-06-07
- Publication Date
- 2025-01-24
Smart Images

Figure BDA0005182884680000321 
Figure BDA0005182884680000351
Abstract
Description
Technical Field
[0001] The present invention relates to an ultraviolet absorbing polyester film, a polarizer protective film, a polarizing plate, and an image display device. Specifically, the present invention relates to an ultraviolet absorbing polyester film using a biomass-derived PET resin, a polarizer protective film having good visibility and few optical defects, and a polarizing plate and an image display device using the same. Background Art
[0002] The polarizing plate used in a liquid crystal display (LCD) is generally composed of a polarizing plate obtained by dyeing polyvinyl alcohol (PVA) or the like with iodine, sandwiched between two polarizing plate protective films. As polarizing plate protective films, triacetylcellulose (TAC) film, PMMA film, and polyethylene terephthalate (PET) film are used. In particular, PET film has low moisture permeability, so it can contribute greatly to improving the durability of LCDs, and is widely used, mainly in large displays.
[0003] When using PET film as a polarizer protective film, rainbow-like color spots may sometimes be generated. It is known that the rainbow-like color spots are caused by the retardation of the PET film and the emission spectrum of the backlight source. By combining a backlight source with a continuous emission spectrum and a PET film with a specific retardation, the PET film can be used as a polarizer protective film.
[0004] On the other hand, such PET films are currently manufactured using resins produced by polycondensing raw materials derived from fossil fuel resources. However, in recent years, in view of global environmental issues such as concerns about the depletion of fossil fuel resources and the increase in carbon dioxide in the atmosphere, there is a global search for alternatives using bioresources.
[0005] The production of ethylene glycol using biomass resources includes a method of producing ethanol from sugar cane, bagasse, carbohydrate crops, etc. by biological treatment methods, and further producing a mixture of ethylene glycol, diethylene glycol, and triethylene glycol through ethylene oxide. The production of terephthalic acid using biomass resources includes, for example, a method of producing xylene by subjecting biomass resources such as wood chips to rapid thermal decomposition with a catalyst, and then producing p-xylene through separation and purification and isomerization treatment, and then subjecting the xylene to a liquid phase oxidation reaction to obtain terephthalic acid.
[0006] Although the raw materials derived from biomass resources thus obtained are subjected to distillation purification and the like to reduce impurities as much as possible, it is known that in addition to the nitrogen contained in the biomass resources, impurities such as nitrogen derived from fermentation bacteria, ammonia, and metal cations are mixed in. Therefore, it is known that the use of polymers derived from biomass resources is prone to frequent occurrence of foreign matter and resin deterioration (for example, Patent Document 1).
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent No. 55729078 Summary of the invention
[0010] Problem that the invention aims to solve
[0011] Terephthalic acid and ethylene glycol derived from biomass resources containing many impurities are usually used after further purification to reduce the amount of impurities, but it is known that even in PET resins produced using such purified dicarboxylic acids and ethylene glycol, the amount of foreign matter that becomes apparent during molding is greater than that of PET resins derived from petroleum. This is particularly a major problem in the production of polarizer protective films because very fine optical defects must be managed.
[0012] Especially when polyester film is used as a polarizer protective film, the addition of ultraviolet absorber to PET resin tends to promote resin degradation. This is particularly true when using PET resin derived from biomass resources.
[0013] The present invention has been made to solve the above problems, and its object is to provide an ultraviolet absorbing polyester film, a polarizing plate, and a display device which have excellent transparency, few foreign matter, good visibility and few optical defects when used as a polarizer protective film even when using a PET resin made of a raw material derived from biomass resources.
[0014] Solutions for solving problems
[0015] The present inventors have conducted intensive research to provide a UV-absorbing polyester film having excellent transparency and less foreign matter even when using a PET resin derived from biomass resources, and in particular, a polarizer protective film having good visibility and less optical defects. As a result, they have found that the deterioration of the PET resin can be greatly suppressed depending on the type of UV absorber. By combining such a UV absorber with a PET resin derived from biomass resources, a polarizer protective film having less foreign matter can be obtained.
[0016] That is, the present invention is as follows.
[0017] Item 1: A polyester film, characterized in that it comprises a layer formed from a biomass polyethylene terephthalate resin composition containing a UV absorber, wherein the biomass polyethylene terephthalate resin composition containing a UV absorber comprises a polyethylene terephthalate resin and a cyclic imide ester-based UV absorber, and the polyethylene terephthalate resin is a polyethylene terephthalate resin in which at least one of ethylene glycol and terephthalic acid is made from biomass resources.
[0018] Item 2: The polyester film according to Item 1, wherein the in-plane retardation is 3,000 to 30,000 nm.
[0019] Item 3: The polyester film according to Item 1 or 2, wherein a ratio of in-plane retardation to thickness direction retardation (Re / Rth) is 0.2 or more and 1.2 or less.
[0020] Item 4: A polyester film according to any one of items 1 to 3, wherein the polyester film has three or more polyester resin layers, the three or more polyester resin layers include a first surface layer present on a first surface, a second surface layer present on a surface on the opposite side thereof, and an intermediate layer, and only the intermediate layer is a layer formed from the biomass polyethylene terephthalate resin composition containing a UV absorber.
[0021] Item 5: The polyester film according to any one of Items 1 to 4, wherein the light transmittance at 380 nm is 20% or less.
[0022] Item 6: The polyester film according to any one of Items 1 to 4, wherein the number of foreign matter having a major diameter of 50 μm or more is 3 to 2000 pieces / 1000 m 2 .
[0023] Item 7: The polyester film according to any one of Items 1 to 6, wherein the polyester film is made of a polyethylene terephthalate resin made from a biomass resource and having a carboxyl terminal concentration of 50 eq / ton or less.
[0024] Item 8: The polyester film according to any one of Items 1 to 7, wherein the carboxyl terminal concentration of the polyethylene terephthalate resin constituting the polyester film is 100 eq / ton or less.
[0025] Item 9: A laminated polyester film comprising a hard coating layer on at least one surface of the polyester film according to any one of Items 1 to 8.
[0026] Item 10: A polarizer protective film comprising the polyester film according to any one of Items 1 to 8 as a base film.
[0027] Item 11: The polarizing plate protective film according to Item 10, which has a hard coat layer.
[0028] Item 12: A polarizing plate comprising the polarizer protective film according to Item 10 or 11 on at least one side of a polarizer.
[0029] Item 13: An image display device comprising the polarizing plate described in Item 12.
[0030] Item 14: The image display device according to Item 13, which is a liquid crystal display device.
[0031] Item 15: The image display device according to Item 13, which is an organic EL display device.
[0032] Effects of the Invention
[0033] According to the present invention, even if a PET resin using a raw material derived from biomass resources is used, a polyester film with high transparency and few foreign matter can be obtained, and in particular, a polarizer protective film and a polarizing plate and an image display device with good visibility and few optical defects can be obtained. This can contribute to solving global environmental problems such as concerns about the depletion of fossil fuel resources and the increase of carbon dioxide in the atmosphere. DETAILED DESCRIPTION
[0034] The present invention is a UV-absorbing polyester film using a polyethylene terephthalate resin (also referred to as "biomass polyethylene terephthalate resin") derived from biomass resources, including a polarizer protective film using the resin as a substrate film. Hereinafter, the polyethylene terephthalate resin is sometimes referred to as a PET resin. In addition, the polyethylene terephthalate resin derived from biomass resources is sometimes referred to as a biomass PET resin. It should be noted that in the present invention, the polarizer protective film may include a functional layer described later. In addition, a polyester film not containing a functional layer is referred to as a polyester substrate film, but the polyester substrate film may include an easy-adhesion layer described later. When referred to as a polyester film, it means a polyester substrate film.
[0035] The biomass PET resin is a PET resin in which at least one of ethylene glycol and terephthalic acid is made of a monomer derived from a biomass resource (as a raw material). It is particularly preferred that the PET resin use ethylene glycol derived from a biomass resource, and preferably 80% by mass or more of the ethylene glycol, more preferably 90% by mass or more, and particularly preferably 100% by mass is derived from a biomass resource. In addition, when terephthalic acid derived from a biomass resource is used, it is also preferred that 80% by mass or more of the terephthalic acid, more preferably 90% by mass or more, and particularly preferably 100% by mass is derived from a biomass resource.
[0036] The polyester film may be a single layer or a multi-layer film. When the polyester film is a multi-layer film, it is preferred that at least one layer contains a PET resin derived from a biomass resource.
[0037] Among the PET resins constituting the polyester film, the biomass PET resin is preferably 70% by mass or more, 80% by mass or more, 90% by mass or more, 95% by mass or more, more preferably more than 95% by mass, further preferably 96% by mass or more, particularly preferably 97% by mass or more, and most preferably 100% by mass.
[0038] In addition, the radiocarbon (C 14 ) is preferably 14% or more, more preferably 16% or more, further preferably 18% or more, particularly preferably 19% or more, and most preferably more than 19%. When only ethylene glycol is used as ethylene glycol, the theoretical upper limit of the carbon content derived from biomass resources is 20%. When terephthalic acid is also used as terephthalic acid, the carbon content derived from biomass resources may exceed 20%, and the higher the better, the most preferred value is 100%, and it may also be 95% or less, 90% or less, 80% or less, or 70% or less.
[0039] Carbon dioxide in the atmosphere contains C in a certain proportion (105.5pMC). 14 Therefore, it is known that plants that grow by taking in atmospheric carbon dioxide, such as corn, have C 14 The content is also about 105.5 pMC. In addition, it is also known that fossil fuels contain almost no C 14 Therefore, by determining the C contained in all carbon atoms in the polyester 14 The biomass content can be calculated by measuring the ratio of carbon derived from biomass resources. 14 ) determination is carried out.
[0040] The polyester film preferably has an in-plane retardation of 2500 to 30000 nm. The lower limit of the in-plane retardation can be 3000 nm, a more preferred lower limit is 4500 nm, a further preferred lower limit is 5000 nm, a particularly preferred lower limit is 6000 nm, and a most preferred lower limit is 7000 nm. When the polyester film is used as a polarizer protective film, by increasing the in-plane retardation, the interference color generated when observed from an oblique direction can be reduced, and good visibility can be ensured. Such a film with high in-plane retardation can be obtained by stretching the uniaxial direction only, or even when biaxially stretched, by making the unidirectional stretching ratio greater than the stretching ratio in the orthogonal direction.
[0041] In addition, when a polarizing plate protective film is used on the visible side of an image display device, when the reflectivity is reduced by providing an anti-reflection layer, etc., interference colors can be suppressed and visibility can be improved even if the in-plane retardation is low. The present invention can also be applied to polyester films having an in-plane retardation of less than 2500 nm, particularly biaxially stretched polyester films.
[0042] The upper limit of the in-plane retardation is more preferably 20000 nm, the further preferred upper limit is 15000 nm, the particularly preferred upper limit is 12000 nm, and the most preferred upper limit is 10000 nm. Even if a polyester film having an in-plane retardation greater than this is used, not only is it not substantially possible to obtain a further improvement in visibility, but the thickness of the film also becomes quite thick, and the operability as an industrial material is reduced, so it is not preferred.
[0043] In addition, the in-plane retardation can also be obtained by measuring the refractive index and thickness in the biaxial directions, and can also be obtained using a commercially available automatic birefringence measuring apparatus such as KOBRA-21ADH (Oji Scientific Instruments Co., Ltd.).
[0044] Polyester film preferably uses ultraviolet absorber. In particular, polarizer protective film is preferably used with ultraviolet absorber for the purpose of suppressing the degradation of optical functional pigments such as iodine pigment in polarizing plate. As ultraviolet absorber, organic ultraviolet absorber and inorganic ultraviolet absorber can be listed, and organic ultraviolet absorber is preferred from the viewpoint of transparency. As organic ultraviolet absorber, benzotriazole series, benzophenone series, cyclic iminoester series and the like and their combination can be listed. In the present invention, the ultraviolet absorber of cyclic iminoester series has the least effect on the degradation of PET resin, so it is preferred.
[0045] Examples of the cyclic iminoester-based ultraviolet absorber include 2,2′-(1,4-phenylene)bis(4H-3,1-benzoxazin-4-one), 2-methyl-3,1-benzoxazin-4-one, 2-butyl-3,1-benzoxazin-4-one, and 2-phenyl-3,1-benzoxazin-4-one, but are not particularly limited thereto.
[0046] Most of the benzotriazole-based and benzophenone-based ultraviolet absorbers have an OH group at the end. This OH group reacts with the carbonyl group of the PET molecule during the melt extrusion process to cause hydrolysis, which promotes the generation of degraded products. Degraded products are particularly likely to be generated in the stagnant part of the resin, and intermittently and continuously flow out from the stagnant part due to the degraded resin, thereby becoming a large amount of black foreign matter and becoming obvious when a film is made. In contrast, the cyclic imidate-based ultraviolet absorber does not have an OH group at the end and is difficult to react with the PET molecule. Although it seems that a part of the ultraviolet absorber decomposes during the melt extrusion process to generate a carboxylic acid end, the reactivity with the PET molecule is lower than that of other ultraviolet absorbers, and it is believed that it is difficult to generate degraded products. The inventors of the present invention have found that by using a cyclic imidate-based ultraviolet absorber, the generation of black foreign matter caused by degraded resin, which is easy to generate when a biomass PET resin is used to make a film, can be suppressed.
[0047] In addition, the cyclic iminoester-based ultraviolet absorber may contain anthranilic acid, its decomposition products, by-products, etc. as raw materials in impurities, and these impurities may also promote the degradation of the resin. The purity of the cyclic iminoester-based ultraviolet absorber is preferably 97.0% by mass or more, more preferably 98.0% by mass or more, further preferably 98.5% by mass or more, particularly preferably 99.0% or more, and particularly preferably 99.5% by mass or more. The purity can be obtained by liquid chromatography.
[0048] In order to maintain a high biomass content of the polyester film, the ultraviolet absorber is preferably added to the layer containing the biomass PET resin. That is, at least one layer of the polyester film is preferably a layer formed of a biomass PET resin composition containing the ultraviolet absorber and the PET resin derived from biomass resources.
[0049] The polyester film may be a single-layer structure consisting of only a layer formed of a biomass PET resin composition, but preferably the polyester film is formed of at least three layers, and the layer formed of the biomass PET resin composition is only an intermediate layer. That is, in a polyester film having three or more layers, the layer of PET resin present on the first surface is the first surface layer, the layer of PET resin present on the opposite surface is the second surface layer, and one or more layers present between the two surface layers are the intermediate layer, preferably, the first surface layer and the second surface layer do not have an ultraviolet absorber, and only the intermediate layer has an ultraviolet absorber.
[0050] In this case, the intermediate layer may be one or more layers. If at least one of the intermediate layers is a layer of the biomass PET resin composition having an ultraviolet absorber, all of the intermediate layers do not need to have an ultraviolet absorber.
[0051] The light transmittance of the polyester film at a wavelength of 380nm is preferably 20% or less. The light transmittance at 380nm is more preferably 15% or less, further preferably 10% or less, and particularly preferably 5% or less. If the light transmittance is 20% or less, the deterioration of the optical functional pigment caused by ultraviolet rays can be suppressed. It should be noted that the light transmittance in the present invention is a value measured by a method perpendicular to the plane of the film, and can be measured using a spectrophotometer (e.g., Hitachi U-3500).
[0052] In order to make the transmittance of the polyester film at a wavelength of 380nm less than 20%, it is ideal to appropriately adjust the ultraviolet absorber, concentration and film thickness. There is no particular limitation on the concentration as long as it is within the range that can obtain the target transmittance, but the lower the concentration, the less influence it has on the deterioration of the PET resin, so it is preferred.
[0053] The content of the ultraviolet absorber in the biomass PET resin composition is preferably 3% by mass or less, more preferably 2% by mass or less, further preferably 1.5% by mass or less, and particularly preferably 1.2% by mass or less. The content of the ultraviolet absorber is preferably 0.1% by mass or more, more preferably 0.2% by mass or more, and further preferably 0.3% by mass or more.
[0054] In addition, in addition to the ultraviolet absorber, it is also a preferred mode to contain various additives other than the catalyst within the range that does not hinder the effect of the present invention. As additives, for example, inorganic particles, heat-resistant polymer particles, alkali metal compounds, alkaline earth metal compounds, phosphorus compounds, antistatic agents, light-resistant agents, flame retardants, heat stabilizers, antioxidants, anti-gelling agents, surfactants, etc. can be listed. In addition, in order to achieve high transparency, it is also preferred that the polyester film does not substantially contain particles. "Substantially free of particles" means that, for example, in the case of inorganic particles, when the inorganic elements are quantified by fluorescent X-ray analysis, the content is less than 50 ppm, preferably less than 10 ppm, and particularly preferably less than the detection limit.
[0055] The number of foreign matter with a major diameter of 50 μm or more present in the polyester film is preferably 2000 pieces / 1000 m 2 The major diameter refers to the maximum distance between any two points on the outer periphery of the cross section of the foreign body when the distance between the two points is measured. If the number of foreign bodies is below the upper limit, there will be no problem of optical defects as a polarizer protective film. The number of foreign bodies with a major diameter of 50 μm or more is more preferably 1000 / 1000m. 2 Below, more preferably 500 pieces / 1000m 2 Below, particularly preferably 100 pieces / 1000m 2 Below, the most preferred is 50 / 1000m 2It is most preferred that there are no foreign particles with a major diameter of 50 μm or more, that is, no foreign particles. From the perspective of productivity, the lower limit of the number of foreign particles can be set to 3 pieces / 1000 m. 2 , and can also be set to 5 / 1000m 2 .
[0056] When the carboxyl terminal concentration of the PET resin is high, it sometimes reacts with the ultraviolet absorber to promote resin degradation. Therefore, the carboxyl terminal concentration of the biomass PET resin used is preferably 50 eq / ton or less, more preferably 45 eq / ton or less, and further preferably 40 eq / ton or less. The preferred concentration is low, and from the perspective of productivity, it is preferably 10 eq / ton or more, more preferably 15 eq / ton or more, and further preferably 20 eq / ton. It should be noted that the determination of the carboxyl terminal concentration of the polyester can be determined by the titration method described below.
[0057] When the layer containing the ultraviolet absorber also contains a PET resin other than that derived from a biomass resource, the preferred range of the carboxyl terminal concentration of the PET resin other than that derived from a biomass resource is also the same.
[0058] The carboxyl terminal concentration of the PET resin constituting the film is preferably 100 eq / ton or less, more preferably 80 eq / ton or less, further preferably 75 eq / ton or less, particularly preferably 70 eq / ton or less, and most preferably 60 eq / ton or less. It should be noted that the lower limit is the same as above.
[0059] If the intrinsic viscosity of the biomass PET resin becomes high, the shear heat generation in the melt kneading process in the film manufacturing process becomes large, and it is sometimes easy to decompose and deteriorate. Therefore, the intrinsic viscosity is preferably 0.8dL / g or less, more preferably 0.75dL / g or less, and further preferably 0.72dL / g or less. From the perspective of film forming properties and maintaining the mechanical strength of the film, the lower limit of the intrinsic viscosity is preferably 0.5dL / g or more, and more preferably 0.55dL / g or more. The range of the intrinsic viscosity of PET resins other than those derived from biomass resources is also the same.
[0060] The intrinsic viscosity of the polyester resin constituting the film is preferably 0.78 dL / g or less, more preferably 0.75 dL / g or less, further preferably 0.72 dL / g or less, and particularly preferably 0.70 or less. The lower limit is the same as above.
[0061] The biomass PET resin is preferably produced using an antimony compound or an aluminum compound as a polymerization catalyst.
[0062] Examples of antimony compounds include antimony trioxide, antimony pentoxide, antimony acetate, antimony glycoxide, etc., preferably antimony trioxide (Sb2O3). The antimony content in the PET resin derived from biomass resources is preferably 80 mass ppm or more, preferably 100 mass ppm or more, and more preferably 120 mass ppm or more, in terms of antimony element. In addition, the antimony content is preferably 330 mass ppm or less, more preferably 300 mass ppm or less, more preferably 270 mass ppm or less, particularly preferably 250 mass ppm or less, and most preferably 220 mass ppm or less, in terms of antimony element.
[0063] As catalysts using aluminum compounds, catalysts disclosed in Japanese Patent Application Laid-Open Nos. 2001-026639 and 2002-322255 can be cited as suitable catalysts. The content of the aluminum compound in the biomass PET resin is preferably 5 mass ppm or more, preferably 7 mass ppm or more, more preferably 10 mass ppm or more, and particularly preferably 15 mass ppm or more, in terms of aluminum element. In addition, the content of the aluminum compound is preferably 50 mass ppm or less, more preferably 40 mass ppm or less, further preferably 30 ppm or less, and particularly preferably 25 mass ppm or less, in terms of aluminum element.
[0064] By setting the content of the antimony compound and the aluminum compound in the above range, the biomass PET resin can be produced with good productivity, and decomposition and degradation during melt mixing with the ultraviolet absorber can be suppressed.
[0065] The type of catalyst and the range of the catalyst content are also the same for PET resins other than those derived from biomass resources.
[0066] When the resin temperature of the film in the melt kneading process in the film manufacturing process is high, the PET resin becomes easy to decompose and deteriorate. The highest temperature reached by the resin in the melt kneading process is preferably below 295°C, more preferably below 290°C, and further preferably below 288°C. The highest temperature reached by the resin is preferably above 270°C, more preferably above 275°C, and further preferably above 280°C. In addition to setting the set temperature of the barrel of the extruder to an appropriate level, the number of rotations is adjusted, the screw structure or the gap between the screw and the barrel is optimized, the filling rate of the resin, the flow rate of the heat medium, etc. are adjusted, and it is preferred that the resin temperature is set in a manner not exceeding the above.
[0067] In addition, it is preferred to minimize the portion where the resin is retained in the path through which the molten resin passes. Specifically, in the extruder, it is preferred to minimize the height difference between the screw elements, the height difference between the blocks of the barrel, and the height difference between the connecting parts of the piping. In addition, it is preferred to set a design that reduces the retention of resin in the piping, the housing of the filter or the filter element, the flow path of the pipe head, etc., or reduce the roughness of these inner walls.
[0068] In addition, when the film is manufactured and the resin extrusion rate is increased, there is a tendency for foreign matter to increase. At these times, it is also preferred to temporarily increase the resin extrusion rate and then reduce it to a specified amount.
[0069] In addition, as a method for blending the ultraviolet absorber into the PET resin, a combination of known methods can be used. For example, a dried ultraviolet absorber can be dry-mixed with a polymer raw material in advance using a kneading extruder to prepare a masterbatch, and the masterbatch can be mixed with a specific polymer raw material during film formation.
[0070] At this time, in order to make the ultraviolet absorber uniformly dispersed and economically blended, the ultraviolet absorber concentration of the masterbatch is preferably set to a concentration of 5 to 30% by mass, and more preferably 7 to 20% by mass. As a condition for making a masterbatch, a mixing extruder is used, and it is preferably extruded for 1 to 15 minutes at an extrusion temperature of more than the melting point of the polyester raw material and less than 290°C, and more preferably 2 to 10 minutes. When it is above 290°C, the weight loss of the ultraviolet absorber is large, and there is a concern that the viscosity of the masterbatch will decrease due to the decomposition of the PET resin. Furthermore, the temperature is preferably 270 to 285°C. When the extrusion time is less than 1 minute, it is sometimes difficult to evenly mix the ultraviolet absorber. At this time, stabilizers, color tone adjusters, and antistatic agents can be added as needed.
[0071] PET resin may also contain other copolymer components. These resins have excellent transparency, and excellent thermal and mechanical properties, and the delay can be easily controlled by stretching. However, by containing copolymer components, the crystallinity is reduced, so it becomes difficult to obtain a high delay. Since the copolymer component is less, it is easier to obtain a large delay even if the thickness is thin, so it is most preferred. When all acid components are set to 100 mol% and all diol components are set to 100 mol%, the total amount of other copolymer components, i.e., acid components other than terephthalic acid and diol components other than ethylene glycol, is preferably 10 mol% or less, more preferably 7 mol% or less, and further preferably 5 mol% or less.
[0072] Furthermore, the polyester film may be subjected to corona treatment, coating treatment, flame treatment, etc. in order to improve the adhesion between the polyester film and the polarizing plate.
[0073] In the present invention, in order to improve the adhesion with the polarizer, it is preferred that at least one side of the polyester film has an easy-adhesive layer with at least one of polyester resin, polyurethane resin or polyacrylic resin as the main component. Here, "main component" refers to a component of more than 50% by mass in the solid component constituting the easy-adhesive layer. The coating liquid used for the formation of the easy-adhesive layer of the present invention is preferably an aqueous coating liquid containing at least one of a water-soluble or water-dispersible copolyester resin, acrylic resin and polyurethane resin. As these coating liquids, for example, water-soluble or water-dispersible copolyester resin solution, acrylic resin solution, polyurethane resin solution, etc. disclosed in Japanese Patent No. 3567927 Gazette, Japanese Patent No. 3589232 Gazette, Japanese Patent No. 3589233 Gazette, Japanese Patent No. 3900191 Gazette, Japanese Patent No. 4150982 Gazette, etc. can be cited.
[0074] The easy-adhesive layer can be obtained by coating the coating solution on one or both sides of a film before stretching or a uniaxially stretched film in the longitudinal direction, drying at 100 to 150°C, and further stretching in the transverse direction. The final coating amount of the easy-adhesive layer is preferably managed to be 0.05 to 0.20 g / m 2 If the coating amount is 0.05g / m 2 On the other hand, if the coating amount is 0.20 g / m 2 When the adhesive layers are provided on both sides of the polyester film, the compositions of the adhesive layers on both sides may be the same or different, and the coating amounts may be the same or different, and may be independently set within the above ranges.
[0075] In order to impart slipperiness, particles are preferably added to the easy-adhesive layer. For the average particle size of the microparticles, from the viewpoint of avoiding them from falling off the covering layer, particles below 2 μm are preferably used. As particles contained in the easy-adhesive layer, for example, inorganic particles such as titanium oxide, barium sulfate, calcium carbonate, calcium sulfate, silicon dioxide, aluminum oxide, talc, kaolin, clay, calcium phosphate, mica, hectorite, zirconium oxide, tungsten oxide, lithium fluoride, calcium fluoride, styrene-based, acrylic acid-based, melamine-based, benzoguanamine-based, silicone-based, etc. can be listed. These can be added to the easy-adhesive layer alone, or two or more can be added in combination.
[0076] As a method for applying the coating liquid, a known method may be used, for example, reverse roll coating, gravure coating, kiss coating, roller brushing, spray coating, air knife coating, wire rod coating, tube scraping, etc., and these methods may be used alone or in combination.
[0077] It should be noted that the average particle size of the above particles is measured by the following method: the particles are photographed using a scanning electron microscope (SEM), and the maximum diameters (the distance between the two points farthest apart) of 300 to 500 particles are measured at a magnification such that the size of the smallest particle is 2 to 5 mm, and the average value is taken as the average particle size.
[0078] The polyester film can be produced by a conventional method for producing a PET film, for example, a method in which a PET resin is melted, extruded in a sheet form, the formed unstretched sheet is stretched in the traveling direction, i.e., the longitudinal direction, by using a roller speed difference at a temperature above the glass transition temperature, then stretched in the transverse direction by using a tenter, and subjected to a heat treatment.
[0079] Polyester film can be a uniaxially stretched film or a biaxially stretched film. When a biaxially stretched film is used as a polarizer protective film, rainbow-like color spots may be observed when the film is observed from an oblique direction, even if no rainbow-like color spots are observed directly above the film surface. Therefore, care must be taken.
[0080] This phenomenon is because the biaxially stretched film is formed by a refractive index ellipsoid with different refractive indices in the longitudinal direction, the width direction, and the thickness direction. According to the transmission direction of the light inside the film, there is a direction in which the delay amount becomes zero (the refractive index ellipsoid looks like a perfect circle). Therefore, if the liquid crystal display screen is observed from a specific direction in the tilted direction, a point where the delay amount becomes zero is sometimes generated, and rainbow-like spots are generated in concentric circles with this point as the center. Moreover, if the angle from just above the film surface (normal direction) to the position where the rainbow-like spots are observed is set to θ, the larger the birefringence in the film surface, the larger the angle θ, and the rainbow-like spots become difficult to observe. There is a tendency for the angle θ to become smaller in the biaxially stretched film, so the uniaxially stretched film is difficult to observe rainbow-like spots and is preferred.
[0081] However, a completely uniaxial (uniaxially symmetrical) film is not preferred because the mechanical strength in the direction orthogonal to the orientation direction is significantly reduced. The present invention preferably has biaxiality (biaxial symmetry) within a range where rainbow-like color spots are not substantially generated or within a range where rainbow-like color spots are not generated within the viewing angle range required by the liquid crystal display screen.
[0082] As a means of maintaining the mechanical strength of the polyester film and suppressing the generation of rainbow spots, it is preferred to control the ratio of the in-plane delay of the polyester film to the delay in the thickness direction (Rth) within a specific range. The thickness direction phase difference refers to the average of the phase differences obtained by multiplying the two birefringences ΔNxz and ΔNyz when the film is observed from a cross section in the thickness direction by the film thickness d. Since the difference between the in-plane delay and the thickness direction delay is smaller, the effect of the birefringence based on the observation angle becomes more isotropic, so the change in delay caused by the observation angle becomes smaller. Therefore, it is believed that rainbow-like color spots caused by the observation angle become difficult to occur.
[0083] The ratio of the in-plane delay to the thickness direction delay of the polyester film (Re / Rth) is preferably greater than 0.200, more preferably greater than 0.500, and further preferably greater than 0.600. The larger the above Re / Rth, the more isotropic the effect of birefringence becomes, and it becomes difficult to produce rainbow-like color spots caused by the observation angle. Moreover, the Re / Rth of a completely uniaxial (uniaxially symmetrical) film is 2.0. However, as mentioned above, as the film approaches a completely uniaxial (uniaxially symmetrical) film, the mechanical strength in the direction orthogonal to the orientation direction is significantly reduced. It should be noted that, as mentioned above, in the case of a biaxially stretched polyester film, Re / Rth can be less than 0.200.
[0084] The Re / Rth of the polyester film is preferably 1.2 or less, and more preferably 1.0 or less. In order to completely suppress the generation of rainbow-like color spots caused by the viewing angle, Re / Rth does not need to be 2.0, and 1.2 or less is sufficient. In addition, even if the above ratio is 1.0 or less, it is sufficient to meet the viewing angle characteristics required by the liquid crystal display device (180 degrees left and right, about 120 degrees up and down).
[0085] If the film-forming conditions of the polyester film are specifically described, the longitudinal stretching temperature and the transverse stretching temperature are preferably 80 to 130°C, and particularly preferably 90 to 120°C. If the stretching ratio is taken as an example of a film with an in-plane retardation of 2500nm to 30000nm and a slow axis in the transverse direction, the longitudinal stretching ratio is preferably 1.0 to 3.5 times, particularly preferably 1.0 to 3.0 times, and the transverse stretching ratio is preferably 2.5 to 6.0 times, particularly preferably 3.0 to 5.5 times. In the case of a film with a slow axis in the longitudinal direction, it is preferred to exchange the longitudinal and transverse ranges. In order to control the retardation within the above range, it is preferred to control the ratio of the longitudinal stretching ratio to the transverse stretching ratio. If the difference between the longitudinal and transverse stretching ratios is too small, it is difficult to increase the retardation, so it is not preferred. In addition, setting the stretching temperature to a lower level is also a preferred approach in terms of increasing the retardation. In the subsequent heat treatment, the treatment temperature is preferably 100 to 250°C, particularly preferably 180 to 245°C.
[0086] In order to suppress the change of retardation, it is preferred that the thickness unevenness of the polyester film is small. Since the stretching temperature and the stretching ratio have a great influence on the thickness unevenness of the film, it is also necessary to optimize the film-making conditions from the viewpoint of thickness unevenness. In particular, if the longitudinal stretching ratio is reduced in order to increase the retardation, the longitudinal thickness unevenness sometimes worsens. The longitudinal thickness unevenness has a very worsened area within a certain specific range of the stretching ratio, so it is desirable to set the film-making conditions outside this range.
[0087] The thickness unevenness of the polyester film is preferably 5.0% or less, more preferably 4.5% or less, further preferably 4.0% or less, and particularly preferably 3.0% or less.
[0088] As mentioned above, in order to control the delay amount of the polyester film within a specific range, it can be carried out by appropriately setting the stretching ratio, stretching temperature, and thickness of the film. For example, the higher the stretching ratio, the lower the stretching temperature, and the thicker the thickness of the film, the easier it is to obtain a high delay amount. On the contrary, the lower the stretching ratio, the higher the stretching temperature, and the thinner the thickness of the film, the easier it is to obtain a low delay amount. However, if the thickness of the film is increased, the thickness direction phase difference tends to become larger. Therefore, the film thickness is expected to be appropriately set to the range described later. In addition, on the basis of the control of the delay amount, it is necessary to consider the physical properties required for processing and set the final film making conditions.
[0089] The thickness of the polyester film is arbitrary, preferably in the range of 15 to 300 μm, more preferably in the range of 20 to 200 μm. Even for a film with a thickness of less than 15 μm, a retardation of more than 3000 nm can be obtained in principle. However, in this case, the anisotropy of the mechanical properties of the film is significant, and it is easy to crack, break, etc., and the practicality as an industrial material is significantly reduced. The lower limit of the particularly preferred thickness is 25 μm. On the other hand, if the upper limit of the thickness of the polyester film exceeds 300 μm, the thickness of the polarizing plate is too thick and not preferred. From the viewpoint of practicality for various uses such as a polarizer protective film, the upper limit of the thickness is preferably 200 μm. The upper limit of the particularly preferred thickness is 100 μm.
[0090] In addition, it is preferred that the polyester film is set to a multilayer structure of at least 3 layers, and an ultraviolet absorber is added to the middle layer of the film. The film of the 3-layer structure in which the middle layer contains an ultraviolet absorber can be specifically made as follows. After the pellets of the polyester used as the outer layer are dried separately, the masterbatch containing the ultraviolet absorber used as the middle layer is mixed with the pellets of the polyester in a specific ratio and dried, it is supplied to a known melt lamination extruder, extruded in a sheet form from a slit-shaped die head, and cooled and solidified on a casting roll to make an unstretched film. That is, using more than 2 extruders, a 3-layer manifold or a confluence block (for example, a confluence block with a rectangular confluence portion), the film layers constituting the two outer layers and the film layers constituting the middle layer are stacked, and a 3-layer sheet is extruded from the tube head, and cooled on a casting roll to make an unstretched film. It should be noted that in the invention, in order to remove foreign matter contained in the PET resin of the raw material that is the cause of optical defects, it is preferably filtered with high precision during melt extrusion. The filter particle size (initial filtration efficiency 95%) of the filter material used for high-precision filtration of the molten resin is preferably 15 μm or less from the viewpoint of ease of removing foreign matter.
[0091] It is also a preferred embodiment that the polyester film has a hard coat layer on at least one side.
[0092] The pencil hardness of the hard coat layer is preferably H or higher, more preferably 2 H or higher. The hard coat layer can be provided by, for example, applying a composition solution of a thermosetting resin or a radiation-curable resin and curing the solution.
[0093] Examples of the thermosetting resin include acrylic resins, urethane resins, phenolic resins, urea-melamine resins, epoxy resins, unsaturated polyester resins, silicone resins, and combinations thereof. In the thermosetting resin composition, a curing agent is added to these curable resins as needed.
[0094] The radiation curable resin is preferably a compound having a radiation curable functional group, and examples of the radiation curable functional group include: ethylenically unsaturated bond groups such as (meth) acryloyl, vinyl, and allyl, epoxy, and oxetanyl. Among them, as the ionizing radiation curable compound, it is preferably a compound having an ethylenically unsaturated bond group, and more preferably a compound having two or more ethylenically unsaturated bond groups, and more preferably a multifunctional (meth) acrylate compound having two or more ethylenically unsaturated bond groups. As the multifunctional (meth) acrylate compound, it can be a monomer, an oligomer, or a polymer.
[0095] Specific examples of these include polyfunctional monomers such as pentaerythritol triacrylate (PETA), dipentaerythritol hexaacrylate (DPHA), pentaerythritol tetraacrylate (PETTA), and dipentaerythritol pentaacrylate (DPPA). In order to adjust the coating viscosity and hardness, monofunctional monomers may be used in combination.
[0096] Examples of the polyfunctional oligomer include polyester (meth)acrylate, urethane (meth)acrylate, polyester-urethane (meth)acrylate, polyether (meth)acrylate, polyol (meth)acrylate, melamine (meth)acrylate, isocyanurate (meth)acrylate, and epoxy (meth)acrylate.
[0097] Examples of the polyfunctional polymer include urethane (meth)acrylate, isocyanurate (meth)acrylate, polyester-urethane (meth)acrylate, and epoxy (meth)acrylate.
[0098] In order to achieve the hardness of the hard coating layer, the monomers having two or more functions in the compound having radiation curable functional groups are preferably 50% by mass or more, and more preferably 70% by mass or more. Furthermore, the monomers having three or more functions in the compound having radiation curable functional groups are preferably 50% by mass or more, and more preferably 70% by mass or more.
[0099] The above-mentioned compound having a radiation-curable functional group may be used alone or in combination of two or more.
[0100] The thickness of the hard coat layer is preferably 0.1 to 100 μm, more preferably 1.0 to 20 μm, and even more preferably 2.0 to 10 μm.
[0101] The refractive index of the hard coat layer is more preferably 1.45 to 1.70, and further preferably 1.50 to 1.60.
[0102] In addition, the refractive index of a hard-coat layer is a value measured under the condition of a wavelength of 589 nm.
[0103] In order to adjust the refractive index of the hard coat layer, there can be mentioned a method of adjusting the refractive index of the resin and a method of adjusting the refractive index of the particles when adding the particles.
[0104] As particles, as low refractive index particles, solid or hollow silica particles, magnesium fluoride particles, etc. can be listed. As high refractive index particles, antimony pentoxide particles, zinc oxide particles, titanium oxide particles, cerium oxide particles, tin-doped indium oxide particles, antimony-doped tin oxide particles, yttrium oxide particles, zirconium oxide particles, etc. can be listed. The average particle size of the primary particles of these particles is preferably 5 to 200 nm, more preferably 8 to 100 nm, and further preferably 10 to 80 nm.
[0105] The particles are more preferably particles surface-treated with a silane coupling agent or the like, and particularly preferably particles surface-treated with a silane coupling agent having a (meth)acryloyl group.
[0106] The polyester film may have an antireflection layer, a low reflection layer, an antiglare layer, an antifouling layer, an antistatic layer, etc. These layers may be provided on the aforementioned hard coating layer, and the hard coating layer may be a layer having these functions, or may constitute a part of these layers. Hereinafter, these layers including the hard coating layer may be referred to as functional layers, and the polyester film laminated with the functional layers may be referred to as a laminated polyester film.
[0107] The low-reflection layer is a layer having a function of reducing the reflectivity by providing a layer with a low refractive index (low-refractive index layer) on the surface of the base film to reduce the refractive index difference with air. The low-refractive index layer is described in the following anti-reflection layer.
[0108] The reflectivity of the laminated polyester film having a low reflection layer is preferably 5% or less, more preferably 4% or less, further preferably 3% or less, particularly preferably 2% or less, and most preferably 1.5% or less when measured from the low reflection layer side. It should be noted that the reflectivity is preferably 0.2% or more.
[0109] The anti-reflection layer is a layer that controls the thickness of the low refractive index layer, and makes the reflected light of the upper interface of the low refractive index layer (the interface of the low refractive index layer-air) interfere with the reflected light of the lower interface of the low refractive index layer (for example, the interface of the substrate film-low refractive index layer) to control the reflection. In this case, the thickness of the low refractive index layer is preferably about the wavelength of visible light (400-700 nm) / (refractive index of the low refractive index layer × 4).
[0110] It is also a preferred embodiment to provide a high refractive index layer between the antireflection layer and the base film. Alternatively, two or more low refractive index layers and high refractive index layers may be provided to further enhance the antireflection effect by multiple interference.
[0111] The reflectance of the laminated polyester film having an antireflection layer is preferably 2% or less, more preferably 1.5% or less, further preferably 1.2% or less, and particularly preferably 1% or less, when measured from the antireflection layer side. The reflectance is preferably 0.1% or more.
[0112] The refractive index of the low refractive index layer is preferably 1.45 or less, and more preferably 1.42 or less. In addition, the refractive index of the low refractive index layer is preferably 1.20 or more, and more preferably 1.25 or more.
[0113] In addition, the refractive index of the low refractive index layer is a value measured under the condition of a wavelength of 589 nm.
[0114] The thickness of low refractive index layer is not limited, usually if suitably set in the range of about 30nm~2μm. In addition, if the interface reflection of the reflection on the surface of low refractive index layer and low refractive index layer and its inner layer (substrate film, hard coat etc.) is offset and further reduce reflectivity for the purpose, then the thickness of low refractive index layer is preferably 70~120nm, more preferably 75~110nm.
[0115] Preferred examples of the low refractive index layer include: (1) a layer formed from a resin composition containing a binder resin and low refractive index particles, (2) a layer formed from a fluorine-based resin as a low refractive index resin, (3) a layer formed from a fluorine-based resin composition containing low refractive index particles, and (4) a thin film of a low refractive index material such as silicon dioxide and magnesium fluoride.
[0116] As the binder resin contained in the resin composition of (1), polyester, polyurethane, polyamide, polycarbonate, acrylic acid, etc. can be used without particular limitation. Among them, acrylic acid is preferred, and a binder resin obtained by polymerizing (crosslinking) a photopolymerizable compound by light irradiation is preferred. The low refractive index particles and the photopolymerizable compound can be listed as those described in the hard coat layer.
[0117] The content of the low refractive index particles in the low refractive index layer is preferably 10 to 250 parts by mass, more preferably 50 to 200 parts by mass, and even more preferably 100 to 180 parts by mass, based on 100 parts by mass of the binder resin.
[0118] As the fluorine-based resin of (2) and (3), a polymerizable compound or a polymer thereof containing at least a fluorine atom in the molecule can be used. As the polymerizable compound, there is no particular limitation, and for example, a polymerizable compound having curing reactive groups such as a photopolymerizable functional group and a thermosetting polar group is preferred. In addition, a compound having these multiple curing reactive groups at the same time can also be used. Relative to the polymerizable compound, the polymer is a polymer that does not substantially have the above-mentioned curing reactive groups, etc.
[0119] The thin film of a low refractive index material such as silicon dioxide or magnesium fluoride in (4) can be formed by a dry process such as vapor deposition, sputtering, or CVD. In addition, a sol-gel method using a silicon dioxide compound is also a preferred method.
[0120] The refractive index of the high refractive index layer is preferably 1.55 to 1.85, more preferably 1.56 to 1.70.
[0121] In addition, the refractive index of the high refractive index layer is a value measured under the condition of a wavelength of 589 nm.
[0122] The thickness of the high refractive index layer is preferably 30 to 200 nm, more preferably 50 to 180 nm. The high refractive index layer may be a plurality of layers, preferably two or less layers, more preferably a single layer. In the case of a plurality of layers, the total thickness of the plurality of layers is preferably within the above range.
[0123] When two high refractive index layers are provided, the refractive index of the high refractive index layer on the low refractive index layer side is preferably increased. Specifically, the refractive index of the high refractive index layer on the low refractive index layer side is preferably 1.60 to 1.85, and the refractive index of the other high refractive index layer is preferably 1.55 to 1.70.
[0124] The high refractive index layer is preferably formed of high refractive index particles and a binder resin. The high refractive index particles and the resin may be those described in the low refractive index layer. Alternatively, the high refractive index particles may be a thin film obtained by a dry process using the metal compound listed as the high refractive index particles.
[0125] Two or more high refractive index particles may be used in combination. In particular, in order to prevent aggregation, it is also preferable to add first high refractive index particles and second high refractive index particles having a smaller surface charge than the first high refractive index particles.
[0126] The content of the high refractive index particles is preferably 30 to 400 parts by mass, more preferably 50 to 200 parts by mass, and even more preferably 80 to 150 parts by mass, based on 100 parts by mass of the resin.
[0127] The high refractive index layer and the low refractive index layer can be formed, for example, by coating a resin composition containing a photopolymerizable compound on a substrate film, drying it, and then irradiating the coated resin composition with light such as ultraviolet rays to polymerize (crosslink) the photopolymerizable compound.
[0128] (Anti-glare layer)
[0129] The anti-glare layer is a layer that prevents the reflection of the light source shape when external light is reflected on the surface or reduces glare by providing irregularities on the surface to cause diffuse reflection.
[0130] The arithmetic mean roughness (Ra) of the concavities and convexities on the surface of the antiglare layer is preferably 0.02 to 0.25 μm, more preferably 0.02 to 0.15 μm, and further preferably 0.02 to 0.12 μm.
[0131] The ten-point average roughness (Rzjis) of the surface irregularities of the antiglare layer is preferably 0.15 to 2.00 μm, more preferably 0.20 to 1.20 μm, and further preferably 0.30 to 0.80 μm.
[0132] Ra and Rzjis are calculated from a roughness curve measured using a contact type roughness meter in accordance with JIS B0601-1994 or JIS B0601-2001.
[0133] As a method of providing an anti-glare layer on a base film, the following methods are mentioned, for example.
[0134] · Coating of anti-glare coatings containing particles (fillers) etc.
[0135] ·Curing the anti-glare layer resin in contact with the mold having a concavo-convex structure
[0136] · Apply the anti-glare layer resin to the mold with a concave-convex structure and transfer it to the base film
[0137] · Coatings that undergo spinodal decomposition during drying and film formation
[0138] The lower limit of the thickness of the antiglare layer is preferably 0.1 μm, and more preferably 0.5 μm. The upper limit of the thickness of the antiglare layer is preferably 100 μm, more preferably 50 μm, and further preferably 20 μm.
[0139] The refractive index of the antiglare layer is preferably 1.20 to 1.80, more preferably 1.40 to 1.70.
[0140] When the refractive index of the anti-glare layer itself is reduced to achieve a low reflection effect, the refractive index of the anti-glare layer is preferably 1.20 to 1.45, and more preferably 1.25 to 1.40.
[0141] When a low refractive index layer described later is provided on the anti-glare layer, the refractive index of the anti-glare layer is preferably 1.50 to 1.80, and more preferably 1.55 to 1.70.
[0142] In addition, the refractive index of the anti-glare layer is a value measured under the condition of a wavelength of 589 nm.
[0143] The low refractive index layer may be provided with irregularities to serve as an antiglare low reflection layer, or the low refractive index layer may be provided on the irregularities to provide an antireflection function to serve as an antiglare antireflection layer.
[0144] When the functional layer is provided by coating, a coating composition to which a solvent and a polymerization initiator are added is used as required on the basis of the particles and resin components constituting these layers. Dispersants, surfactants, antistatic agents, silane coupling agents, thickeners, coloring inhibitors, colorants (pigments, dyes), defoamers, leveling agents, flame retardants, ultraviolet light absorbers, tackifiers, inhibitors, antioxidants, surface modifiers, and lubricants may be further added to the coating composition. In addition, for the purpose of improving fingerprint resistance, it is also preferred to appropriately add a known polysiloxane-based or fluorine-based antifouling agent.
[0145] The haze of the laminated polyester film is 2% or less, which is also a preferred embodiment. The haze is more preferably 1.5% or less, further preferably 1.2% or less, and particularly preferably 1.0% or less. The haze is preferably 0.01% or more, more preferably 0.1% or more. By setting the above range, when the laminated polyester film is used as a polarizer protective film, a highly transparent and clear image can be obtained.
[0146] In order to make the haze of the laminated polyester film fall within the above-mentioned range, the following methods are preferably adopted: reducing the particle size of the hard coating layer, etc.; filtering to remove coarse particles after the particles are fully dispersed; selecting a combination of particles and resins that are not easy to agglomerate when drying; selecting a combination of resins and solvents that are not easy to roughen the surface when drying and adjusting the drying conditions, etc.
[0147] In order to make the haze of the laminated polyester film fall within the above range, the haze of the base film is preferably also within the above range. Methods for making the haze of the base film fall within the above range include: reducing the amount of lubricant particles added to the original film; making the original film a multilayer structure and adding lubricant particles only to the surface layer; adding lubricant particles to the easy-adhesion layer without adding lubricant particles to the original film. In addition, by setting the amount of the metal compound of the catalyst to the above range, the generation of foreign matter from the catalyst can be suppressed, thereby suppressing the increase in haze.
[0148] Furthermore, in the production of thin films, the melted resin is extruded in a sheet form on a cooling roll. If the cooling speed is slow, the haze of the film may increase. In particular, when there are many foreign matters and a large amount of catalyst, PET resin derived from biomass resources tends to be easily crystallized. It is preferable to adopt measures such as lowering the temperature of the cooling roll and blowing cold air to the opposite side of the cooling roll to increase the cooling speed.
[0149] The haze can be measured in accordance with JIS-K7105 using a turbidity meter (NHD2000, manufactured by Nippon Denshoku Industries).
[0150] In the present invention, the polyester film is preferably a roll-shaped long film wound on a core. The length of the long film is preferably 500m or more and 20000m or less, more preferably 1000m or more and 10000m or less. The width is preferably 300mm or more and 10000mm or less, more preferably 500mm or more and 8000mm or less. In addition, the laminated polyester film is also the same.
[0151] The polarizing plate has a structure in which one side or both sides of the polarizing plate are bonded with a polarizing plate protective film. Preferably, at least one of the polarizing plate protective films constituting the polarizing plate is a polyester film using a biomass PET resin. Among them, it is preferred that only one side of the polarizing plate is set as a polarizing plate protective film of a biomass PET film. On the other hand, the surface of the other side of the polarizing plate can be a resin film such as triacetyl cellulose, acrylic, polycyclic olefin, a coating layer of a curable resin, or a structure in which these films and / or coating layers are not provided. Furthermore, on the other side of the polarizing plate, a layer with a phase difference can be provided as a polarizing plate laminated with an optical compensation layer. The optical enhancement layer can include those that are given a phase difference by stretching the aforementioned triacetyl cellulose, acrylic, polycyclic olefin, etc. resin films, and coating layers that orient liquid crystal compounds. In addition, the layer with a phase difference can be set as a λ / 4 wavelength layer as a circular polarizing plate. The polarizing plate may be a stretched film obtained by dyeing PVA or the like with iodine or a dichroic organic dye, for example, or may be an oriented film of a liquid crystal compound containing a dichroic dye, a wire grid polarizing plate, or the like.
[0152] The image display device is not particularly limited as long as it is an image display device using a polarizing plate, such as a liquid crystal display device, an organic EL display device, or a micro LED display device.
[0153] In the image display device, the polarizer protective film of the present invention is preferably disposed on the opposite side to the image display unit with respect to the polarizer.
[0154] The liquid crystal display device has at least a backlight source and a liquid crystal unit disposed between two polarizing plates as components, and may also have other components such as a color filter, a lens film, a diffusion sheet, an anti-reflection film, etc. as appropriate.
[0155] As the backlight structure, it can be a side-light type using a light guide plate, a reflector, etc. as components, or it can be a direct-light type. The liquid crystal display device preferably uses a white light source as the backlight source. The white light source can list a white light-emitting diode that emits white light by combining a blue light using a compound semiconductor or a light-emitting diode that emits ultraviolet light with a phosphor as a suitable light source. The combination with the phosphor can list a combination with a yellow phosphor to become white light, a combination with a green phosphor and a red phosphor to become white light, etc. As a yellow phosphor, it can list: yttrium / aluminum / garnet yellow phosphors, terbium / aluminum / garnet systems. As a green phosphor, it can list: Eu-activated chlorosilicate phosphors, Eu-activated silicate phosphors, Eu-activated β-sialon phosphors, Eu-activated thiogallate phosphors, rare earth aluminate phosphors, silicon nitride lanthanum phosphors, perovskite phosphors, etc. Examples of the red phosphor include manganese ion-activated fluoride phosphors, Eu-activated calcium silicate phosphors, nitride phosphors, Eu-activated fluorine oxygen coordinated phosphor (FOLP) phosphors, and perovskite-type phosphors.
[0156] In addition, a white light source formed by a light source that emits excitation light and a light-emitting layer of quantum dots is also a preferred light source. As quantum dots, there are QDEF from Nanosys. TM 、QD Vision's Color IQ TM Etc. A light-emitting layer composed of a combination of green quantum dots and the aforementioned red phosphor may be used, or a light-emitting sheet including a magenta diode composed of a combination of the aforementioned blue diode and red phosphor and green quantum dots may be used.
[0157] In organic EL display devices and micro LED display devices, a circular polarizing plate is used on the visible side of the image display device for the purpose of preventing reflection.
[0158] Example
[0159] Hereinafter, examples are given to more specifically illustrate the present invention, but the present invention is not limited to the following examples, and can also be implemented by applying appropriate changes within the scope of the gist of the present invention, which are all included in the technical scope of the present invention. It should be noted that the evaluation method of the physical properties in the following examples is as described below.
[0160] (1) In-plane retardation (Re)
[0161] In-plane retardation refers to a parameter defined by the product (ΔNxy×d) of the orthogonal biaxial refractive index anisotropy (ΔNxy=|Nx-Ny|) on the film and the film thickness d (nm), which is a measure of optical isotropy and anisotropy. The biaxial refractive index anisotropy (ΔNxy) is obtained by the following method. Two polarizing plates are used to determine the orientation axis direction of the film, and a 4cm×2cm rectangle is cut out in a manner orthogonal to the orientation axis direction as a measurement sample. For this sample, an Abbe refractometer (manufactured by ATAGO, NAR-4T, measurement wavelength 589nm) is used to determine the orthogonal biaxial refractive index (Nx, Ny) and the refractive index in the thickness direction (Nz), and the absolute value of the biaxial refractive index difference (|Nx-Ny|) is used as the refractive index anisotropy (ΔNxy). The film thickness d (nm) was measured using an electric micrometer (Millitron 1245D manufactured by FEINPRUF) and the unit was converted to nm. The in-plane retardation (Re) was calculated from the product (ΔNxy×d) of the refractive index anisotropy (ΔNxy) and the film thickness d (nm).
[0162] (2) Thickness retardation (Rth)
[0163] The thickness direction retardation is a parameter representing the average of the retardation obtained by multiplying the two birefringences ΔNxz (|Nx-Nz|) and ΔNyz (|Ny-Nz|) by the film thickness d when observing from a cross section in the film thickness direction. The thickness direction retardation (Rth) is obtained by calculating the average of (ΔNxz×d) and (ΔNyz×d) by the same method as the measurement of the retardation by obtaining Nx, Ny, Nz and the film thickness d (nm).
[0164] (3) Transmittance at a wavelength of 380 nm
[0165] The light transmittance of each film in the wavelength range of 300 to 500 nm was measured using a spectrophotometer (U-3500, manufactured by Hitachi, Ltd.) with the air layer as a reference, and the light transmittance at a wavelength of 380 nm was determined.
[0166] (4) Evaluation of resin degradation
[0167] 9 g of PET resin and 1 g of ultraviolet absorber were placed in an ampoule tube, heated at 290°C for 10 minutes under vacuum, and stirred at 290°C for 10 minutes. Thereafter, the temperature was kept constant for 2 hours while purging with nitrogen to obtain a masterbatch. The intrinsic viscosity of the PET resin before treatment and the intrinsic viscosity of the masterbatch after treatment were measured, and the degree of deterioration was evaluated from the difference in intrinsic viscosity before and after treatment (ΔIV).
[0168] (5) Carboxyl terminal concentration (AV)
[0169] The film and the raw material polyester resin were measured by the following method: In the case of the polyester resin, the fragments were directly used as samples, and in the case of the polarizing plate protective film, the coating was scraped with a knife as a sample.
[0170] i. Sample preparation
[0171] About 3g of the sample is frozen and crushed, and after vacuum drying for 24 hours at 70°C, a balance is used to weigh in the range of 0.20±0.0005g. The mass at this time is set to W (g), 10ml of benzyl alcohol and the weighed sample are added to the test tube, and the test tube is immersed in a benzyl alcohol bath heated to 205°C, and the sample is dissolved while stirring with a glass rod. The sample when the dissolution time is 3 minutes, 5 minutes, and 7 minutes is set to A, B, and C respectively. Then, a new test tube is prepared, only benzyl alcohol is put into it, and the same steps are used to process, and the sample when the time is 3 minutes, 5 minutes, and 7 minutes is set to a, b, and c respectively. However, when there are inorganic particles in the sample, the value after removing the mass of the inorganic particles is W (g). It should be noted that the content of inorganic particles can be obtained by dissolving the sample with a solvent, recovering the solid component by centrifugation, and measuring the mass.
[0172] ii. Titration
[0173] Titrate with a 0.04 mol / l potassium hydroxide solution (ethanol solution) with a known factor. Phenol red is used as the indicator, and the moment when the color changes from yellow-green to light red is taken as the end point. The titration amount (ml) of the potassium hydroxide solution is calculated. The titration amount of samples A, B, and C is set as XA, XB, and XC (ml), and the titration amount of samples a, b, and c is set as Xa, Xb, and Xc (ml)
[0174] iii. Calculation of carboxyl terminal concentration
[0175] The titration amount XA, XB, and XC for each dissolution time were used to determine the titration amount V (ml) at a dissolution time of 0 minutes by the least square method. Similarly, the titration amount V0 (ml) was determined using Xa, Xb, and Xc. Next, the carboxyl terminal concentration was determined according to the following formula.
[0176] Carboxyl terminal concentration (eq / ton) = [(V-V0) × 0.04 × NF × 1000] / W
[0177] NF: Factor of 0.04 mol / l potassium hydroxide solution
[0178] (6) Intrinsic viscosity (IV)
[0179] 0.20 g of the freeze-pulverized and dried sample obtained by setting the carboxyl terminal concentration in the same manner as above was weighed, and 20 ml of a mixed solvent of 1,1,2,2-tetrachloroethane and p-chlorophenol in a mass ratio of 1:3 was used, and the mixture was stirred at 100°C for 60 minutes to completely dissolve, and the mixture was cooled to room temperature and passed through a glass filter to prepare a sample. Using an Ubbelohde viscometer (manufactured by Rigo Co., Ltd.) adjusted to 30°C, the falling time of the sample and the solvent was measured, and the intrinsic viscosity [η] was calculated by the following formula.
[0180] [η]=(-1+√(1+4K'ηSp)) / 2K'C
[0181] ηSp=(τ-τ0)τ0
[0182] Here,
[0183] [η]: Intrinsic viscosity (dl / g)
[0184] ηSp: Specific viscosity (-)
[0185] K': Huggins constant (= 0.33)
[0186] C: concentration (=1g / dl)
[0187] τ: Sample drop time (sec)
[0188] τ0: solvent falling time (sec)
[0189] (7) Biomass
[0190] According to ASTM D6866-16 Method B (AMS), the radiocarbon (C 14 ) determination is carried out.
[0191] (8) Evaluation of the number of foreign matter in the film
[0192] Use a defect inspection machine (MaxEye.CORE / 160C manufactured by FUTEC) to screen the scratches and internal foreign matter by judging them in black and white. Take samples from the corresponding positions, and if they are foreign matter, measure the long diameter with a laser microscope. Calculate the area with more than 20 foreign matter with a long diameter of 50μm or more per 1000m 2 The number of.
[0193] (9) Rainbow spot observation
[0194] A PET film produced by the method described below is adhered to one side of a polarizer containing PVA and iodine in such a way that the absorption axis of the polarizer is perpendicular to the orientation axis of the film, and a TAC film (manufactured by Fujifilm Co., Ltd., thickness 80 μm) is adhered to the opposite side to produce a polarizing plate. The polarizing plate on the visible side of a liquid crystal display device using a white LED as a light source is peeled off, and the white LED includes a light-emitting element composed of a combination of a blue light-emitting diode and a yttrium / aluminum / garnet-based yellow phosphor, and the polarizing plate obtained by bonding is replaced, so that the PET film on the light-emitting side becomes the visible side and the absorption axis of the polarizing plate becomes the same direction as the original polarizing plate. At an angle of about 50 degrees to the normal direction of the screen of the manufactured liquid crystal display device, the orientation is changed from the long side direction of the screen to the short side direction and visually observed, and the presence or absence of rainbow spots is determined according to the following method.
[0195] ◎: No rainbow spots are produced from any direction.
[0196] ○: Very light rainbow spots or coloring are observed in some locations.
[0197] △: Light rainbow spots or coloring are observed in some locations.
[0198] ×: Rainbow spots or coloring are clearly observed in some locations.
[0199] (10) Content of metal elements in resin
[0200] The polyester resin described below was weighed in a platinum crucible, carbonized in an electric furnace, and then ashed at 550°C for 8 hours in a muffle furnace. The ashed sample was dissolved in 1.2M hydrochloric acid to prepare a sample solution. The prepared sample solution was measured under the following conditions, and the concentration of antimony in the polyester resin was obtained by high-frequency inductively coupled plasma emission spectrometry. In addition, the concentration of aluminum can be obtained by the same method as above.
[0201] Device: CIROS-120 manufactured by SPECTRO
[0202] Plasma output: 1400W
[0203] Plasma gas: 13.0L / min
[0204] Auxiliary gas: 2.0L / min
[0205] Atomizer: Cross flow atomizer
[0206] Chamber: Cyclone chamber
[0207] Measurement wavelength: 167.078nm
[0208] (11) Haze
[0209] The haze of the film was measured using a turbidity meter (NHD2000, manufactured by Nippon Denshoku Industries) in accordance with JIS-K7136.
[0210] (12) Reflectivity
[0211] The 5-degree reflectance at a wavelength of 550 nm was measured from the surface on the antireflection layer side (or low reflection layer side) using a spectrophotometer (manufactured by Shimadzu Corporation, UV-3150). It should be noted that the surface opposite to the side on which the antireflection layer (or low reflection layer) of the polyester film is provided was painted with a black mark, and then a black polyvinyl chloride tape (polyvinyl chloride tape HF-737 manufactured by Kyowa Co., Ltd., width 50 mm) was attached and measured.
[0212] Production Example 1 (Production of Polyethylene Terephthalate Resin A)
[0213] The esterification reactor was heated, and when it reached 200°C, 86.4 parts by mass of terephthalic acid derived from petroleum and 64.6 parts by mass of ethylene glycol derived from petroleum were added, and 0.017 parts by mass of antimony trioxide, 0.064 parts by mass of magnesium acetate tetrahydrate, and 0.16 parts by mass of triethylamine were added as catalysts while stirring. Next, the pressure was increased and the temperature was increased, and the pressure esterification reaction was carried out under the conditions of a gauge pressure of 0.34 MPa and 240°C. The esterification reactor was returned to normal pressure and 0.014 parts by mass of phosphoric acid was added. Furthermore, it took 15 minutes to increase the temperature to 260°C, and 0.012 parts by mass of trimethyl phosphate was added. Then, after 15 minutes, a high-pressure disperser was used for dispersion treatment. After 15 minutes, the obtained esterification reaction product was transported to a polycondensation reactor, and a polycondensation reaction was carried out at 280°C under reduced pressure.
[0214] After the polycondensation reaction is completed, the mixture is filtered using a Naslon filter having a 95% cutoff diameter of 5 μm, extruded from a nozzle into a strand, cooled and solidified using cooling water that has been pre-filtered (pore size: 1 μm or less), and cut into pellets. The obtained polyethylene terephthalate resin (A) has an intrinsic viscosity of 0.62 dl / g, a carboxyl terminal concentration of 30 eq / ton, an antimony content of 135 mass ppm, and substantially no inactive particles or internal precipitated particles. Hereinafter, polyethylene terephthalate resin A is referred to as PET (A).
[0215] Production Example 2 (Production of Polyethylene Terephthalate Resin B)
[0216] 10 parts by mass of a dried cyclic imine ester-based ultraviolet absorber (2,2'-(1,4-phenylene)bis(4H-3,1-benzoxazin-4-one) (ultraviolet absorber a) and 90 parts by mass of PET (A) containing no particles were mixed and a polyethylene terephthalate resin (B) containing a cyclic imine ester-based ultraviolet absorber was obtained using a kneading extruder. Hereinafter, the polyethylene terephthalate resin B is abbreviated as PET (B).
[0217] In the production of PET (B), an ultraviolet absorber having a purity of 99.5% or more is used, the resin temperature in the kneading extruder is controlled not to exceed 285°C, and the kneading time is about 5 minutes.
[0218] Production Example 3 (Production of Polyethylene Terephthalate Resin C)
[0219] A polyethylene terephthalate resin (C) having an intrinsic viscosity of 0.62 dl / g, a carboxyl terminal concentration of 35 eq / ton, an antimony element content of 135 mass ppm in the resin, and substantially no inactive particles and internal precipitated particles was obtained by the same method as in Production Example 1 except that ethylene glycol was derived from biomass. Hereinafter, the polyethylene terephthalate resin C is referred to as PET (C). The biomass degree of the obtained PET (C) is 19% or more.
[0220] Production Example 4 (Production of Polyethylene Terephthalate Resin D)
[0221] Except for using PET (C), a polyethylene terephthalate resin (C) containing a cyclic imine ester ultraviolet absorber was obtained by the same method as in Production Example 2. Hereinafter, the polyethylene terephthalate resin D is abbreviated as PET (D).
[0222] Production Example 5 (Production of Polyethylene Terephthalate Resin E)
[0223] 10 parts by weight of benzotriazole-based ultraviolet absorber (ultraviolet absorber b) 2-(5-chloro-2H-benzotriazole-2-yl)-6-(1,1-dimethylethyl)-4-methylphenol (ultraviolet absorber b) and 90 parts by weight of PET (C) were mixed and a mixing extruder was used to obtain a polyethylene terephthalate resin (E) containing a benzotriazole-based ultraviolet absorber. Hereinafter, polyethylene terephthalate resin E is abbreviated to PET (E).
[0224] Production Example 6 (Production of Polyethylene Terephthalate Resin F)
[0225] 10 parts by weight of a benzotriazole-based ultraviolet absorber 2-[2-hydroxy-3,5-bis(α,α-dimethylbenzyl)phenyl]benzotriazole (ultraviolet absorber c) and 90 parts by weight of PET (C) were mixed and a mixing extruder was used to obtain a polyethylene terephthalate resin (F) containing a benzotriazole-based ultraviolet absorber. Hereinafter, polyethylene terephthalate resin F is abbreviated to PET (F).
[0226] Production of adhesive modified coating liquid
[0227] A water-dispersible copolyester resin containing a sulfonic acid metal salt group was prepared by carrying out an ester exchange reaction and a polycondensation reaction by a conventional method, wherein the composition of the water-dispersible copolyester resin was 46 mol% of terephthalic acid, 46 mol% of isophthalic acid and 8 mol% of sodium 5-sulfoisophthalate as dicarboxylic acid components (relative to the total dicarboxylic acid components), and 50 mol% of ethylene glycol and 50 mol% of neopentyl glycol as diol components (relative to the total diol components). Next, 51.4 parts by mass of water, 38 parts by mass of isopropyl alcohol, 5 parts by mass of n-butyl cellosolve and 0.06 parts by mass of a nonionic surfactant were mixed, and the mixture was heated and stirred. When the mixture reached 77° C., 5 parts by mass of the water-dispersible copolyester resin containing a sulfonic acid metal salt group was added thereto. The mixture was stirred until the resin lumps disappeared, and then the resin aqueous dispersion was cooled to room temperature to obtain a uniform water-dispersible copolyester resin liquid having a solid content concentration of 5.0% by mass. Furthermore, 3 parts by mass of aggregated silica particles (Fuji Silysia Chemical, Silysia 310) were dispersed in 50 parts by mass of water, and then 0.54 parts by mass of an aqueous dispersion of Silysia 310 was added to 99.46 parts by mass of the above-mentioned water-dispersible copolyester resin liquid, and 20 parts by mass of water was added while stirring to obtain an adhesion-modified coating liquid.
[0228] Resin degradation evaluation 1
[0229] Using the PET (A) resin pellets and the ultraviolet absorber (a), resin degradation evaluation was carried out.
[0230] Resin Degradation Evaluation 2
[0231] Using PET (C) resin pellets and the ultraviolet absorber (a), resin degradation evaluation was carried out.
[0232] Resin Deterioration Evaluation 3
[0233] Using the PET (C) resin pellets and the ultraviolet absorber (b), resin degradation evaluation was carried out.
[0234] Resin Deterioration Evaluation 4
[0235] Using PET (C) resin pellets and the ultraviolet absorber (c), resin degradation evaluation was carried out.
[0236] [Table 1]
[0237] PET resin UV absorber ΔIV(dl / g) Rating 1 A a 0.16 Rating 2 C a 0.18 Rating 3 C b 0.28 Rating 4 C c 0.33
[0238] The results of the resin degradation evaluation are shown in Table 1. Compared with Evaluation 1, the resin degradation of Evaluation 2 was slightly greater. This is considered to be because the use of ethylene glycol derived from biomass resources increased impurities and promoted the resin degradation caused by the ultraviolet absorber. In addition, compared with Evaluation 2, the resin degradation of Evaluation 3 and Evaluation 4 was very large. This is considered to be because the ultraviolet absorber (b) and the ultraviolet absorber (c) containing an OH group at the end promoted the degradation of the PET resin.
[0239] Example 1
[0240] 90 parts by weight of particle-free PET (C) resin pellets and 10 parts by weight of PET (D) resin pellets containing an ultraviolet absorber, which are raw materials for the intermediate layer of the substrate film, are dried under reduced pressure (1 Torr) at 135°C for 6 hours and then supplied to extruder 2 (for intermediate layer II). In addition, PET (A) is dried by a common method and supplied to extruder 1 (for outer layer I and outer layer III) respectively to be dissolved.
[0241] The two polymers were filtered using a filter material of a stainless steel sintered body (nominal filtration accuracy 95% retention of 10μm particles), stacked in two three-layer confluence blocks, extruded from a pipe head in sheet form, and then wound on a casting drum with a surface temperature of 30°C using an electrostatic casting method. Air at 20°C was blown from the opposite side to cool and solidify it to produce an unstretched film. At this time, the discharge volume of each extruder was adjusted so that the thickness ratio of layer I, layer II, and layer III was 10:80:10. The temperature of the resin in the extruder was adjusted so as not to exceed 285°C. In addition, the assembly was performed in a manner that the connecting parts of the extruder screw, the barrel, and the resin piping did not produce a height difference. In addition, the filter housing is designed so that resin retention is not likely to occur.
[0242] Next, the coating was dried by a reverse roll method to a coating weight of 0.08 g / m 2 The adhesiveness-modifying coating solution was applied to both sides of the unstretched PET film and then dried at 80° C. for 20 seconds.
[0243] The unstretched film with the coating layer formed thereon was guided to a tenter stretching machine, and while holding the ends of the film with a clamp, it was guided to a hot air zone at a temperature of 125°C and stretched to 4.0 times in the width direction. Then, the film was treated at a temperature of 225°C for 30 seconds while maintaining the stretched width in the width direction, and then subjected to a 3% relaxation treatment in the width direction, to obtain a uniaxially oriented PET film with a film thickness of 50 μm.
[0244] Example 2
[0245] A uniaxially oriented PET film was obtained in the same manner as in Example 1 except that the thickness of the unstretched film was changed to about 100 μm.
[0246] Example 3
[0247] The unstretched film produced by the same method as in Example 2 is heated to 105°C using a heated roller group and an infrared heater, and then stretched 1.5 times in the travel direction using a roller group with a circumferential speed difference, and then stretched 4.0 times in the width direction using the same method as in Example 1 to obtain a biaxially oriented PET film with a film thickness of 50 μm.
[0248] Example 4
[0249] By the same method as in Example 3, the film was stretched 2.0 times in the traveling direction and 4.0 times in the width direction to obtain a biaxially oriented PET film having a film thickness of about 50 μm.
[0250] Example 5
[0251] By the same method as in Example 3, the film was stretched 3.3 times in the traveling direction and 4.0 times in the width direction to obtain a biaxially oriented PET film having a film thickness of 75 μm.
[0252] Example 6
[0253] By the same method as in Example 3, the film was stretched 4.0 times in the traveling direction and 1.0 times in the width direction to obtain a uniaxially oriented PET film having a film thickness of 100 μm.
[0254] Example 7
[0255] By the same method as in Example 3, the film was stretched 3.8 times in the traveling direction and 4.0 times in the width direction to obtain a biaxially oriented PET film having a film thickness of 50 μm.
[0256] Example 8
[0257] By the same method as in Example 3, the film was stretched 3.8 times in the traveling direction and 3.6 times in the width direction to obtain a uniaxially oriented PET film having a film thickness of 50 μm.
[0258] Comparative Example 1
[0259] A uniaxially oriented PET film having a film thickness of 50 μm was obtained by the same method as in Example 1, using 90 parts by mass of PET (C) resin pellets containing no particles and 10 parts by mass of PET (E) resin pellets containing an ultraviolet absorber as raw materials for the intermediate layer of the substrate film.
[0260] Comparative Example 2
[0261] By the same method as in Example 2, 90 parts by mass of non-particle-containing PET (C) resin pellets and 10 parts by mass of ultraviolet absorber-containing PET (F) resin pellets were used as raw materials for the intermediate layer of the substrate film to obtain a uniaxially oriented PET film with a film thickness of 50 μm.
[0262] Table 2 shows the evaluation results of the polyester films of Examples 1 to 8 and Comparative Examples 1 and 2.
[0263] [Table 2]
[0264]
[0265] As shown in Table 2, the films of Examples 1 to 8 had a small number of foreign matter and high transparency. On the other hand, the films of Comparative Examples 1 and 2 had a large number of foreign matter. This is believed to be because the ultraviolet absorber containing an OH group at the end promoted the degradation of the PET resin. In addition, the film with an in-plane retardation of 3000 nm or more also showed good results in the observation of rainbow spots.
[0266] Production Example of Polarizer Protective Film Having Hard Coat Layer
[0267] Preparation Example of Coating Liquid for Hard Coat Layer Formation
[0268] The following coating materials were mixed to prepare a coating liquid for forming a hard coat layer.
[0269] Methyl ethyl ketone: 65.00 mass%
[0270] Dipentaerythritol hexaacrylate: 27.20 mass%
[0271] (A-DPH manufactured by Shin-Nakamura Chemical)
[0272] Polyethylene glycol diacrylate: 6.80 mass%
[0273] (A-400 manufactured by Shin-Nakamura Chemical)
[0274] Photopolymerization initiator: 1.00 mass%
[0275] (Irgacure 184 manufactured by Ciba Specialty Chemicals)
[0276] Preparation Example of Coating Liquid for Forming Low Refractive Index Layer
[0277] 2,2,2-trifluoroethyl acrylate (45 parts by mass), perfluorooctyl ethyl acrylate (45 parts by mass), acrylic acid (10 parts by mass), azoisobutyronitrile (1.5 parts by mass), and methyl ethyl ketone (200 parts by mass) were added to a reaction container, and reacted at 80° C. for 7 hours under a nitrogen atmosphere to obtain a methyl ethyl ketone solution of a polymer having a weight average molecular weight of 20.000. The obtained polymer solution was diluted with methyl ethyl ketone to a solid content concentration of 5% by mass to obtain a fluoropolymer solution.
[0278] The obtained fluoropolymer solutions were mixed in the following manner to obtain a coating liquid for forming a low refractive index layer.
[0279] Fluoropolymer solution: 44 parts by mass
[0280] 1,10-bis(2,3-epoxypropoxy)-2,2,3,3,4,4,5,5,6,6,7,7,8,8,9,9-hexafluorodecane (Fluorite FE-16 manufactured by Kyoeisha Chemical Co., Ltd.): 1 part by mass
[0281] Triphenylphosphine: 0.1 parts by mass
[0282] Methyl ethyl ketone: 19 parts by mass
[0283] Preparation Example of Coating Liquid for Forming High Refractive Index Layer
[0284] 80 parts of methyl methacrylate, 20 parts of methacrylic acid, 1 part of azoisobutyronitrile, and 200 parts of isopropyl alcohol were added to a reaction container, and reacted at 80° C. for 7 hours under a nitrogen atmosphere to obtain an isopropyl alcohol solution of a polymer having a weight average molecular weight of 30,000. The obtained polymer solution was further diluted with isopropyl alcohol to a solid content of 5% to obtain an acrylic resin solution B. Next, the obtained acrylic resin solution was mixed with the following components to obtain a coating solution for forming a high refractive index layer.
[0285] Acrylic resin solution: 5 parts by mass
[0286] Bisphenol A diglycidyl ether: 0.25 parts by mass
[0287] Titanium oxide particles with an average particle size of 20 nm: 0.5 parts by mass
[0288] Triphenylphosphine: 0.05 parts by mass
[0289] Isopropyl alcohol: 14.25 parts by mass
[0290] Example of manufacturing surface-processed thin films
[0291] Example 9
[0292] The hard coat layer-forming coating solution was applied to one side of the polyester film obtained in Example 1, and dried at 70°C for 1 minute to remove the solvent. The film coated with the hard coat layer was then irradiated with ultraviolet light using a high-pressure mercury lamp to form a hard coat layer with a thickness of 5 μm, thereby obtaining a laminated polyester film having a hard coat layer.
[0293] The high refractive index layer-forming coating liquid obtained by the above method was then applied to the hard coat layer, and dried at 150° C. for 2 minutes to form a high refractive index layer with a film thickness of 0.1 μm. The low refractive index layer-forming coating liquid H obtained by the above method was then applied to the high refractive index layer, and dried at 150° C. for 2 minutes to form a low refractive index layer with a film thickness of 0.1 μm, thereby obtaining a laminated polyester film having an antireflection layer.
[0294] Example 10
[0295] The coating liquid for forming a low refractive index layer obtained by the above method was applied to the hard coat surface of the hard coat layer laminated polyester film obtained above, and dried at 150° C. for 2 minutes to form a low refractive index layer with a film thickness of 2 μm, thereby obtaining a laminated polyester film with an antireflection layer.
[0296] Embodiment 11
[0297] A laminated polyester film having an antireflection layer was obtained in the same manner as in Example 9 except that the polyester film of Example 7 was used as the base material.
[0298] Example 12
[0299] A laminated polyester film having an antireflection layer was obtained in the same manner as in Example 9 except that the polyester film of Example 8 was used as the base material.
[0300] Table 3 shows the evaluation results of the laminated polyester films of Examples 9 to 12.
[0301] [Table 3]
[0302]
[0303] Industrial Applicability
[0304] According to the present invention, even if a PET resin using raw materials derived from biomass resources is used, a polyester film with high transparency and few foreign matter can be obtained, and a polarizer protective film, a polarizing plate, and a liquid crystal display device with good visibility and few optical defects can be obtained. Furthermore, the polyester film of the present invention exhibits good ultraviolet absorption, and in addition to the use of polarizer protective film, it can also be used for surface protection films of touch panel substrates, image display devices, etc., anti-scattering films, laminating films for windows, etc., and decorative films. As a result, it can help solve global environmental problems such as concerns about the depletion of fossil fuel resources and the increase of carbon dioxide in the atmosphere, and the industrial applicability is extremely high.
Claims
1. A polyester film, characterized in that The invention discloses a layer formed of a biomass polyethylene terephthalate resin composition containing a UV absorber, wherein the biomass polyethylene terephthalate resin composition containing a UV absorber comprises a polyethylene terephthalate resin and a cyclic imide ester-based UV absorber, wherein the polyethylene terephthalate resin is a polyethylene terephthalate resin in which at least one of ethylene glycol and terephthalic acid is made from biomass resources. 2 . The polyester film according to claim 1 , wherein the in-plane retardation is 3,000 to 30,000 nm. 3 . The polyester film according to claim 1 , wherein a ratio of in-plane retardation to thickness direction retardation (Re / Rth) is 0.2 or more and 1.2 or less.
4. The polyester film according to any one of claims 1 to 3, wherein The polyester film has three or more polyester resin layers, wherein the three or more polyester resin layers include a first surface layer present on a first surface, a second surface layer present on a surface opposite thereto, and an intermediate layer, and only the intermediate layer is a layer formed of the biomass polyethylene terephthalate resin composition containing an ultraviolet absorber. 5 . The polyester film according to claim 1 , which has a light transmittance at 380 nm of 20% or less.
6. The polyester film according to any one of claims 1 to 4, wherein The number of foreign matter with a long diameter of 50 μm or more is 3 to 2000 pieces / 1000 m 2 .
7. The polyester film according to any one of claims 1 to 6, wherein The polyester film is formed of a polyethylene terephthalate resin made from biomass resources and having a carboxyl terminal concentration of 50 eq / ton or less.
8. The polyester film according to any one of claims 1 to 7, wherein The carboxyl terminal concentration of the polyethylene terephthalate resin constituting the polyester film is 100 eq / ton or less. 9 . A laminated polyester film comprising a hard coating layer on at least one surface of the polyester film according to claim 1 . 10 . A polarizer protective film comprising the polyester film according to claim 1 as a base film. 11 . The polarizing plate protective film according to claim 10 , which has a hard coat layer. 12 . A polarizing plate comprising the polarizer protective film according to claim 10 or 11 on at least one side of a polarizer. 13 . An image display device comprising the polarizing plate according to claim 12 .
14. The image display device according to claim 13, which is a liquid crystal display device. 15 . The image display device according to claim 13 , which is an organic EL display device.
Citation Information
Patent Citations
Polymerization catalyst and preparation process for polyester and polyester prepared using the catalyst
JP2001026639A
Method for producing polyester
JP2002322255A